Konsep Wajah dan Strategi Kesantunan dalam Ekspresi Kausatif Benefaktif Bahasa Jepang: Kajian Sosiopragmatik - Iriantini, Sri (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2026)
The concept of face is the basis of the language politeness strategies, including positive faces and negative faces, which is important in the use of language as a means of communication. Meanwhile, benefactive causative expressions are expressions that are also related to politeness in language, because there is a context related to the concept of faces in it and there is also the use of keigo in benefactive verbs. Politeness in Japanese reflects the condition of Japanese society that upholds politeness in society, with the concept of uchi-soto. The method used in this study is a qualitative descriptive method, with sociopragmatic approach that observes language as a means of communication associated with the social condition of the community. The results showed that the concept of face found in this research was a positive face concept if the relationship between the speaker and the hearer was close (uchi group), and the speaker needed to be recognized, while the concept of negative face was often found if the kinship relationship between the speaker and the hearer was not close (soto group), and the speaker had a desire to be independent. For politeness strategies used by speakers in saving faces, there are positive politeness strategies in the utterances that express the speaker's help or empathy for the speaker, and negative politeness strategies if the speaker feels disturbed and has a desire to be free.